Research progress on the role of mindfulness in intervention for adolescent obesity - Shao, Shuming; Li, Linda; Zhang, Yimin; Liu, Zheng; Zhang, Xiaorui (Frontiers in Endocrinology, 2024)
In the face of the increasingly serious background of overweight and obesity rates among adolescents in China, mindfulness, as an emerging therapeutic approach, has shown its unique effectiveness. This article reviewed the research progress of mindfulness in the intervention of adolescent obesity, summarized its effects on improving physiological and psychological indicators, and listed the different options for implementing mindfulness therapy. These studies supported the preliminary effectiveness of mindfulness in the intervention of adolescent obesity, providing a basis for mindfulness to become a new approach for obesity intervention in the future.